Theorising the responsibility to protect - Thakur, Ramesh Chandra, 1948-; Maley, William, 1957- (Cambridge : Cambridge University Press, 2015)
One of the most important developments in world politics in the last decade has been the spread of the idea that state sovereignty comes with responsibilities as well as privileges, and that there exists a global responsibility to protect people threatened by mass atrocities. The principle of the Responsibility to Protect is an acknowledgment by all who live in zones of safety of a duty of care towards those in zones of danger. Thakur and Maley argue that this principle has not been discussed sufficiently in the context of international and political theory, in particular the nature and foundations of political and international order and the strength and legitimacy of the state. The book brings together a range of authors to discuss the different ways in which the Responsibility to Protect can be theorised, using case studies to locate the idea within wider traditions of moral responsibilities in international relations.
Part I. Context -- 1. Introduction: theorising global responsibilities / Ramesh Thakur and William Maley -- 2. The evolution of the responsibility to protect: from concept and principle to actionable norm / Gareth Evans -- 3. From the right to persecute to the responsibility to protect: Feuerbachian inversions of rights and responsibilities in state-citizen relations / Charles Sampford and Ramesh Thakur -- 4. Responsibility to protect and a theory of norm circulation / Amitav Acharya -- Part II. The Responsibility to Protect, Normative Theory, and Global Governance -- 5. Responsibility to protect and world order / Tim Dunne -- 6. International law and the responsibility to protect / Michael Byers -- 7. The Responsibility to protect, multilateralism and international legitimacy / Edward Newman -- 8. Global governance and the responsibility to protect / Abiodun Williams -- 9. International law, the responsibility to protect and international crises / Jean-Marc Coicaud -- 10. The Responsibility to protect and the just war tradition / Alex J. Bellamy -- 11. War is not the answer: the responsibility to protect and military intervention / Jonathan Graubart -- Part III. The Responsibility to Protect and International Social Purposes -- 12. United Nations peacekeeping and the responsibility to protect / Mats Berdal -- 13. Humanitarian law, refugee protection and the responsibility to protect / William Maley -- 14. Is the responsibility to protect doctrine gender-neutral? / Susan Harris Rimmer -- 15. The responsibility to protect: a western idea? / Jacinta O'Hagan -- 16. Colonialism and the responsibility to protect / Siddharth Mallavarapu.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Responsibility to protect (International law); Humanitarian intervention